Sensitivity of the Saline Load Test for Traumatic Arthrotomy of the Ankle: Simulation Among 42 Patients Undergoing Ankle Arthroscopy. Issue 3 (14th September 2018) - Bohl, Daniel; Frank, Rachel; Lee, Simon; Hamid, Kamran; Holmes, George; Lin, Johnny; Lee, Simon
Category: Ankle Introduction/Purpose: The saline load test is routinely used to evaluate for traumatic arthrotomy in orthopaedics. The purpose of this study was to determine the volume of saline required to detect traumatic arthrotomy of the ankle. Methods: 42 patients undergoing elective ankle arthroscopy were prospectively enrolled. For each patient, a standard 4 mm anteromedial portal was established. Next, an 18-guage needle was inserted at the site of the anterolateral portal. Sterile saline was slowly injected through the needle until saline extravasated from the anteromedial portal. Saline volumes at the time of extravasation were recorded and analyzed. Results: The saline volume required to achieve extravasation ranged from 0.2mL-60.0 mL (Figure 1A). The median saline volume required to achieve extravasation (and interquartile range) was 9.7 mL (3.8-29.6 mL); however, five of 42 patients required volumes between 50.0 mL and 60.0 mL. A total of 50.0 mL was required to achieve 90% sensitivity, 55.0 mL to achieve 95% sensitivity, and 60.0 mL to achieve 99% sensitivity (Figure 1B). Conclusion: The previously recommended 30 mL of saline required to reliably detect traumatic arthrotomy of the ankle may be too small a volume. The present study suggests that clinicians should attempt to inject 60 mL in order to effectively rule out a traumatic arthrotomy injury.